2015
DOI: 10.3390/catal5041797
|View full text |Cite
|
Sign up to set email alerts
|

Part II: Oxidative Thermal Aging of Pd/Al2O3 and Pd/CexOy-ZrO2 in Automotive Three Way Catalysts: The Effects of Fuel Shutoff and Attempted Fuel Rich Regeneration

Abstract: Abstract:The Pd component in the automotive three way catalyst (TWC) experiences deactivation during fuel shutoff, a process employed by automobile companies for enhancing fuel economy when the vehicle is coasting downhill. The process exposes the TWC to a severe oxidative aging environment with the flow of hot (800 °C-1050 °C) air. Simulated fuel shutoff aging at 1050 °C leads to Pd metal sintering, the main cause of irreversible deactivation of 3% Pd/Al2O3 and 3% Pd/CexOy-ZrO2 (CZO) as model catalysts. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Small Pd peak intensities in Pd catalysts indicated that small Pd To verify the reduction properties of the Pd catalysts, H2-TPR analysis was performed, and the results are shown in Figure 4. All the prepared Pd catalysts showed negative peaks in the range of 60 to 90 °C, which is related to formation of PdHx before the analysis began [13][14][15]. Each Pd catalyst showed a different intensity of this negative PdHx peak in the 60 to 90 °C range, where the intensity was the smallest for Pd/CeO2 and the largest for Pd/SiO2.…”
Section: Characterization Of Supports and Pd Catalystsmentioning
confidence: 97%
See 1 more Smart Citation
“…Small Pd peak intensities in Pd catalysts indicated that small Pd To verify the reduction properties of the Pd catalysts, H2-TPR analysis was performed, and the results are shown in Figure 4. All the prepared Pd catalysts showed negative peaks in the range of 60 to 90 °C, which is related to formation of PdHx before the analysis began [13][14][15]. Each Pd catalyst showed a different intensity of this negative PdHx peak in the 60 to 90 °C range, where the intensity was the smallest for Pd/CeO2 and the largest for Pd/SiO2.…”
Section: Characterization Of Supports and Pd Catalystsmentioning
confidence: 97%
“…The Pd/CeO2 and Pd/SiO2 samples exhibited positive peak regions at approximately 300 and 700 °C, and 750 °C, respectively. These positive peaks indicated that bulk PdOx species were reduced to Pd 0 or hydrogen spillover [15,16]. To verify the reduction properties of the Pd catalysts, H 2 -TPR analysis was performed, and the results are shown in Figure 4.…”
Section: Characterization Of Supports and Pd Catalystsmentioning
confidence: 99%
“…For instance, larger-size Pd particles have higher H 2 storage capacity, and therefore exhibit higher intense negative peaks, whereas smaller-size Pd particles exhibit low intense negative peaks owing to their lower H 2 storage capacity. Similarly, β-PdH formed by the larger-size Pd particles decomposes at lower temperatures, whereas the β-PdH formed by the smaller-size Pd particles decomposes at higher temperatures [31,32]. Hence, one can confirm that the obtained negative H 2 consumption peak is due to the decomposition of Pd hydrate species formed at ambient temperature (i.e., during the H 2 purge prior to TPR analysis).…”
Section: Influence Of Calcination Temperaturementioning
confidence: 71%
“…In a companion paper [6], Zheng et al investigate Pd (another major TWC component generally responsible for oxidation reactions) in the context of fuel shutoff influence and possibilities of rich regeneration. In contrast to Rh, Pd deactivation is mainly due to Pd metal sintering resulting in irreversible deactivation for both Pd/Al 2 O 3 and Pd/Ce x O y -ZrO 2 catalysts.…”
Section: This Special Issuementioning
confidence: 99%